Investigating Clinical Failure of Bone Grafting through a Window at the Femoral Head Neck Junction Surgery for the Treatment of Osteonecrosis of the Femoral Head. - Wei Zuo; Wei Sun; Dingyan Zhao; Fuqiang Gao; Yangming Su; Zirong Li (PLoS ONE, 2016)
AIMS:This study aimed to analyze the clinical factors related to the failure of bone grafting through a window at the femoral head-neck junction. METHODS:In total, 119 patients (158 hips) underwent bone grafting for treatment of avascular necrosis of the femoral head. The patients were classified by their ARCO staging and CJFH classification. All patients were clinically and radiographically followed up every three months during the first year and every six months in the following year. The clinical follow-up comprised determination of pre- and postoperative Harris hip scores, while serial AP, frog lateral radiographs, and CT scan were used for the radiographic follow-up. RESULTS:The clinical failure of bone grafting was observed in 40 patients. The clinical failure rates in patients belonging to ARCO stage II period, IIIa, and III (b + c) were 25.9%, 16.2%, and 61.5%, respectively, while those in patients belonging to (C + M + L1) type and L2, L3 type disease groups were 1.7%, 38.9%, and 39%, respectively. The clinical failure rates in patients aged below 40 and those aged 40 and over were 20.5% and 39.0%, respectively (all P < 0.05). CONCLUSION:Disease type, disease stage, and patient age are risk factors for failure of bone graft surgery. Patients belonging to ARCO stage II and IIIa showed a good overall response rate, while patients belonging to ARCO stage IIIb and IIIc and those with necrotic lesions involving the lateral pillar (L2 and L3 type) showed high surgical failure rates.